Bahasa dalam Era Kecerdasan Buatan: Implikasi Filsafati terhadap Pemahaman Makna dan Komunikasi - Sukisno (Indonesian Journal of Applied Linguistics Review, 2023)
This study aims to examine the impact of artificial intelligence (AI) on the understanding of meaning and communication processes within the field of language. As AI usage continues to grow across various platforms—such as chatbots and virtual assistants—it becomes increasingly important to explore how this technology affects patterns of human interaction. Data were collected from 45 participants through questionnaires and in-depth interviews designed to uncover users' experiences with AI and the challenges they encountered. The findings reveal that although the majority of respondents are satisfied with AI’s ability to deliver information, there are significant shortcomings in its understanding of context and linguistic nuances. Only about 30% of respondents believe that AI can truly grasp deeper meanings. The study also incorporates philosophical implications concerning the authority of meaning, authenticity in communication, and identity in digital interactions. These results offer valuable insights for technology developers to enhance AI's capacity to comprehend social and emotional contexts, while also helping the public to better understand the limitations and potential of AI in communication. Consequently, this research contributes to a deeper understanding of the interconnectedness between language, technology, and philosophy in the digital age.